Film breakup of tilted impinging spray under various pressure conditions. (February 2020) - Xiao, Di; Yukihiko, Ichikawa; Li, Xuesong; Hung, David; Nishida, Keiya; Xu, Min
Fuel film on engine walls caused by spray impingement would dramatically cause engine friction deterioration, incomplete combustion, and significant cycle-to-cycle variations. In a previous work, it has been demonstrated that fuel film would break up via wave entrainment induced by the high-speed coflow. Meanwhile, the film breakup dynamics depend on various boundary conditions, such as injection pressure, ambient pressure, and so on. However, such impact on the wall film formation was not investigated thoroughly in existing literature. This work aims to perform a parameter study to investigate possible means to enhance wave entrainment effect as to reduce the amount of impingement fuel mass. In this study, simultaneous measurements of macroscopic structure and its corresponding footprint of impinging spray are conducted using a single-hole, prototype injector in a constant volume chamber. The macroscopic spray structure was captured by high-speed backlit imaging, and the film was obtained using laser-induced fluorescence under different conditions. The laser-induced fluorescence signal is converted to film thickness following a calibration procedure where laser-induced fluorescence signals from a series of known-thickness film are captured. A mathematical processing method is used to analyze both the dynamic behavior of film thickness and amount of droplet detachment caused by high-speed coflow. It is found that at the leading edge of film waves, a remarkable amount of liquid droplets detaches from the liquid film and the quantity of film mass on the wall decreases during this process. Quantitative analysis is conducted and the mass ratio of detached droplets over residual liquid film is estimated. We hold that the film breakup percentage increases with both ambient and injection pressure due to the enhanced high-speed coflow. Then, variation laws for various boundary conditions are obtained based on the observations.